2020
DOI: 10.1001/jamanetworkopen.2020.24385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Secondhand Smoke Exposure in New York City Public Housing After Implementation of the 2018 Federal Smoke-Free Housing Policy

Abstract: IMPORTANCE Secondhand smoke (SHS) exposure is associated with many health conditions in children and adults. Millions of individuals in the US are currently exposed to SHS in their homes. OBJECTIVE To investigate whether a federal ban on smoking in public housing settings was associated with a decrease in indoor SHS levels in New York City public housing developments 12 months after the policy's implementation. DESIGN, SETTING, AND PARTICIPANTS This cohort study tracked indoor air quality longitudinally from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
(77 reference statements)
2
23
1
Order By: Relevance
“…One year after the SFH policy went into effect, NYCHA residents and staff reported widespread smoking violations. The findings are consistent with our one-year pre-post longitudinal analysis of trends in objectively measured indoor exposure to SHS levels in NYCHA buildings, which demonstrated little change in air nicotine and PM 2.5 in nonsmokers’ households and common areas [ 12 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One year after the SFH policy went into effect, NYCHA residents and staff reported widespread smoking violations. The findings are consistent with our one-year pre-post longitudinal analysis of trends in objectively measured indoor exposure to SHS levels in NYCHA buildings, which demonstrated little change in air nicotine and PM 2.5 in nonsmokers’ households and common areas [ 12 ].…”
Section: Discussionsupporting
confidence: 89%
“…We are conducting a longitudinal natural experiment to assess the impact of HUD’s SFH policy on SHS exposure among residents living in New York City Housing Authority (NYCHA), the nation’s largest PHA. Using state-of-the art air monitoring procedures, 12 months after the policy came into effect, we found little change in the airborne nicotine concentration and particulate matter (PM 2.5 ) in nonsmoker apartments and common areas of NYCHA buildings compared with baseline measures [ 12 ]. The small number of studies that have examined air quality impacts of SFH policy have similarly demonstrated a modest and/or non-significant reduction in SHS exposure [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…After each laboratory calibration, the Airbeam units were deployed in a large, natural experiment evaluating the impact of new smoke-free housing (SFH) policies on air quality in public housing units every 6 months. 11,23 Due to the onset of the COVID-19 pandemic, we were unable to perform Airbeam sensor calibration 24 months post-SFH policy implementation (April-September 2020). A calibration technical error for select Airbeam 2 sensors occurred at 30 months post-SFH policy (December-March 2021), leading to their exclusion from data analysis at that timepoint.…”
Section: Field Sampling Periodsmentioning
confidence: 99%
“…10 In tandem, public housing authorities (PHAs) have been federally mandated to implement smoke-free housing (SFH) policies in their developments. [11][12][13] Despite policy implementation in July 2018, there is still some evidence of cigarette smoking within New York City Housing Authority (NYCHA) developments. 11 Stemming from a larger, quasi-experimental study evaluating the impact of SFH policies on secondhand smoke exposure in select NYCHA buildings, we utilized a network of low-cost sensors to evaluate indoor PM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation